A detailed study of the coupling between Dielectric Resonators and various excitation systems for the design and execution of microwaves integrated circuits for useing them communications devices (Journal of Hama University, 2019)
Generally, dielectric resonances that operate in traditional modes such as TE, TM, HEM are often used for the design and execution of active and passive circuits. However, within the high-frequency (microwave-optical) beam, the Dielectric resonators operating in these conventional modes are of relatively small dimensions, so their precise accuracy in these circuits is very difficult and is not easily integrated into these circuits.Therefore, the use of these resonators has been used to operate with new modes called Whispering Modes WM because they allow increasing the diameter of the resonator for the same previous frequencies. This is more appropriate and more suitable for circuit design, especially microwaves  passive integrated circuits such as: Combinor of puissance, Filters, Oscillators, etc.... The research here focuses on a detailed digital electromagnetic study of the coupling between cylindrical dielectric resonators operating in these modes and various excitation systems.The completion of this study required us to use a numerical method of calculation based on library MODULEF programme, which is the Finite elements method in three-dimensions and free oscillations and force, after writing all the necessary and appropriate codes for each structure studied. This study will define accurately for all electromagnetic parameters (compounds and distribution of electromagnetic fields - resonance frequencies of modes - transport coefficients S12, external quality coefficient Qe etc ...). This study will put all the values ​​of the electromagnetic parameters in our hands as a function of the geometrical properties and the systems of excitation of the studied structures, and through this we can choose the most appropriate ways to design and execute the practical circuits to use them in the appropriate applications. As far as we are concerned, these results will be used in the design and execution of microwave band pass filters in very low loss, narrow band and excellent selectivity.